Picosecond photochemistry of a cofacial diporphyrin containing iron(III) and zinc(II): Mimicking electron transfer between cytochrome c and the primary electron donor in reaction centers of photosynthetic bacteria - Fujita, I. (1982)
Comparison of picosecond kinetic and spectroscopic data for Zn octaethylporphine and Fe(III)Cl octaethylporphine with that for Zn—Fe(III)Cl, a cofacial diporphyrin composed of a Zn porphyrin covalently bound to an Fe(III)Cl porphyrin with two chains of five atoms each, supports the assignment of a light-driven electron transfer (k > 10(11)s(-1)) within Zn—Fe(III)Cl to form [Zn(+)·—Fe(II)]Cl. The kinetics (k ≈ 10(10)s(-1)) and thermodynamics of the reverse electron transfer are compared to those of a similar electron transfer in bacterial photosynthesis, the reduction of an oxidized bacteriochlorophyll dimer, (BChl)(2)(+)·, by Fe(II) cytochrome c.